Competitiveness of Ghana’s Upstream Petroleum Fiscal Regime: Fit for Purpose? - Acheampong, T.; Ali-Nakyea, A. (Petroleum Resource Management in Africa, 2023)
This chapter assesses the attractiveness of Ghana’s upstream petroleum fiscal regime against key features of optimal fiscal policy, namely: efficiency of targeting economic rents, risk sharing, neutrality and progressiveness. We also identify potential fiscal reform options that Ghana can consider in optimising its fiscal regime. Various full lifecycle cash flow models are estimated using three oil field sizes—large (750 mmboe), medium (250 mmboe), small (50 mmboe)—with different cost profiles and four different pre- and post-Jubilee contract terms. Our results show that Ghana’s fiscal regime is investor-friendly with an average effective tax rate (AETR) or government take of 51.38% from royalties, IOC income taxes, and additional oil entitlements (AOE). The inclusion of the State’s Carried and Participating Interest (state take) pushes the AETR into the 65%–75% range, comparable with 65%–85% IMF benchmark values. In the context of Ghana’s low resource base, this balances the trade-offs between investment promotion and securing revenues to the State, especially when compared with other countries in the region and beyond. Also, we find that Ghana’s hybrid fiscal regime is regressive at the lower end of the oil price scale if oil prices are below $60/bbl while being slightly progressive with increasing oil prices above $60/bbl. In terms of the windfall tax structure, simulations using four tax scenarios indicate that the current AOE regime underperforms on the size and timing of revenues generated to the State. The windfall tax regime can be vastly simplified and at the same time accrue more revenues to the State by reducing the current five tiers to one: using a higher top headline rate while also lowering the trigger threshold. Furthermore, Ghana can also consider introducing targeted fiscal packages aimed at maximising economic recovery of over 500 mmboe of stranded reserves. Finally, we note significant institutional challenges regarding the capacity of some State agencies to efficiently and effectively monitor petroleum costs. In the absence of a change to the fiscal regime, the ability of Ghana’s regulatory and commercial institutions to monitor and audit costs will determine the extent to which the nation will generate significant revenues beyond just royalties and State participation.
Research Article
Keywords: upstream petroleum fiscal regime; optimal fiscal policy; Ghana